Radioprotection in the 21st Century - J. Lakota (Вестник войск РХБ защиты)
In nature, there are bacteria and eukaryotic multicellular organisms (insects, arthropods) that have extraordinary, nevertheless still poorly understood radiation resistance. Knowledge of its mechanisms can significantly increase the effectiveness of radioprotectors and can lead to fundamental discoveries for the radioprotection in humans.Relevance. The growing threat of nuclear war and nuclear accidents requires updating and deepening the knowledge of the occurrence of radiation resistance in nature and the development of pharmaceutical means for human radiation protection.The purpose of the study is to summarize the ideas available in the scientific literature about the mechanisms of increased radiation resistance of some living organisms and about modern radioprotectors.The source base of the study. Scientific publications available through the biomedical research database PubMed. Research method. Analytical.Discussion. The reasons for the high radioresistance of the bacterium Deinococcus radiodurans and scorpions of the genus Androctonus are considered. For D. radiodurans, the radioresistance is based on the ability to protect its proteome, and not the genome, as previously thought. The resistance of bacterial cells to radiation is regulated by manganese antioxidants. With this ability, D. radiodurans can repair up to 500 breaks, while E. coli can repair two or three DNA breaks at once. The new bioconcept can be expressed as “Primacy of the proteome over the genome”. The principle of the radioresistance of scorpions is less clear. It is known that the main role is played by the hemolymph cells the anulocytes (“hémocytes annelés”), and hemocyanin molecules present freelely in the hemolymph. The paper further describes general therapeutic approaches to the development of new radioprotective agents. Radioprotectors are supposed to prevent/inhibit the formation of free radicals caused by radiation (most of which are formed during radiolysis of water), thereby inhibiting their reactions with biomolecules reducing the frequency of DNA strand breaks and preventing the occurrence of cellular disorders. The classification of radioprotectors is given, their properties are described in detail.Conclusions. For the future development of radioprotectors, it is important to recognize the “new” paradigm of radioresistance – the “primacy of the proteome over the genome”. From today's practical point of view, the cytoprotective complexing drug Amifostine can be recommended in radiation protection.